Thermal Transport Properties of Two-Dimensional Janus MoXSiN2 (X = S, Se, and Te) - Gan, Siyu (Langmuir : the ACS journal of surfaces and colloids, 2024)
The design of Janus materials offers an effective means of regulating both their physical and chemical properties, leading to their application in various fields. However, the underlying mechanism governing the modulation of the thermal transport characteristics through the construction of Janus materials remains unclear. In this work, we introduce VI-group elements into the MoSi2N4 structure, yielding two-dimensional Janus MoXSiN2 (X = S, Se, and Te) and systematically investigate their thermal transport properties based on first-principles calculation methods. Our findings reveal that the lattice thermal conductivities (κl) of MoSSiN2, MoSeSiN2, and MoTeSiN2 are 47.2, 24.3, and 40.6 W/mK at 300 K, respectively, significantly lower than that of MoSi2N4 (224 W/mK). Such low κl values mainly come from the introduction of X atoms, which enhances phonon scattering and reduces phonon vibration frequencies. In addition, MoTeSiN2 exhibits a higher κl compared to MoSeSiN2, contrary to the trend observed in most materials containing VI-group elements, where κl decreases gradually from S to Te. This anomalous behavior can be attributed to the competitive result between its lower phonon vibrational frequency and weaker phonon anharmonicity of MoTeSiN2. This work elucidates the inherent mechanism governing the modulation of thermal transport properties in Janus materials, thereby enhancing the potential application of Janus MoXSiN2 in engineering thermal management